Light luminescence and trapping in polydimethylsiloxane foils with low concentration of gold nanoparticles. Issue 1 (1st February 2022) - Torrisi, L.; Cutroneo, M.; Silipigni, L.; Fazio, B.; Di Marco, G.; Slepicka, P.; Fajstavr, D.; Torrisi, A.
Abstract : Light trapping and luminescence have been observed in polydimethylsiloxane (PDMS) foils containing about 0.1–0.2 wt% gold nanoparticles (AuNPs). The so-prepared PDMSs have been physically characterized using SEM microscopy, UV–Vis, FTIR and Raman spectroscopies. The used AuNPs have been controlled by means of the surface plasmon resonance absorption spectra. In the AuNPs–PDMS foils, a luminescence peak at about 425 nm has been induced by an exciting light at 280 nm. The light injection with an optical fiber is trapped inside the polymer-containing NPs and illuminates all the polymer volume. The measurements of scattered light show an increment in the light intensity due to the presence of AuNPs and air bubbles inducing diffractions, reflections and Mie scattering. Further investigations have been conducted irradiating the PDMS with AuNPs in vacuum with 2.9 MeV proton beams producing luminescence in the blue region. The mechanisms of light trapping and luminescence and the possible applications of the prepared material are presented and discussed.